Sustainability of PCM-lime mortars for heritage retrofitting: Carbon footprint and impact on energy demand across climates - Pavia, Sara (My University, 2025)
Recent research on PCM–lime mortars has predominantly addressed material-scale behaviour or single-climate cases, with limited integration of embodied carbon and operational energy at the building scale—particularly for heritage envelopes under conservation constraints. To address this gap, the present study develops a climate-resolved, building-scale assessment that couples cradle-to-gate embodied impacts with operational energy effects for PCM-enhanced lime mortars in heritage retrofitting. Specifically, cradle-to-gate global warming potential (A1–A3) is combined with a screening-level estimate of operational energy savings (B6) over a 50-year service life. Three PCMs were examined: two paraffin-based (melting points of 18 °C and 24 °C) and one bio-based, derived from agricultural by-products (melting point of 29 °C). These were integrated into lime mortars and modelled across three retrofit strategies—internal grouting, internal rendering, and a combined approach—applied to the 13th-century Hermitage of Santa Brígida (Spain), with extrapolation to all Spanish climate zones to assess performance under varying thermal conditions. Simulations reveal that PCM-enhanced mortars can eliminate cooling demands and significantly reduce heating needs. Maximum total carbon footprint reductions were achieved with the bio-based PCM (89.1 %), followed by the 24 °C paraffin PCM (87.2 %) and the 18 °C paraffin PCM (74.6 %), depending on the climate zone. This work provides a comparative assessment of paraffin versus bio-based PCMs, highlighting the importance of climate-PCM compatibility and delivering critical insights into the embodied carbon and long-term environmental impact of these mortars in heritage retrofitting.
PUBLISHED
Keywords: Phase Change Materials (PCMs); Lime mortar; Carbon footprint; Energy efficiency; Sustainability